Prevalence and characteristics of covert contraceptive use in the Performance Monitoring for Action multi-country study - Dana O. Sarnak; Elizabeth Gummerson; Shannon N. Wood; Funmilola M. OlaOlorun; Simon Peter Sebina Kibira; Linnea A. Zimmerman; Philip Anglewicz (Elsevier, 2022)
Objectives: A more nuanced understanding of contributors to covert contraceptive use remains critical to protecting covert users and reducing its necessity. This study aimed to examine the overall prevalence of covert use, and sociodemographic characteristics associated with covert vs overt use across multiple geographies in sub-Saharan Africa and Asia. Study Design: Performance Monitoring for Action (PMA) is one of the few nationally representative surveys that measures covert use across socially diverse contexts via a direct question. Utilizing PMA 2019-2020 phase 1 data from Burkina Faso, Côte D'Ivoire, Kenya, Democratic Republic of Congo (DRC; Kinshasa and Kongo Central regions), Uganda, Nigeria (Kano and Lagos), Niger, and Rajasthan, we estimated overall prevalence of covert use. We conducted bivariate analyses and multivariate logistic regressions for 6 sites, comparing the odds of covert use with overt use among users of contraception by sociodemographic characteristics. Results: Covert use ranged from 1% in Rajasthan to 16% in Burkina Faso. Marital status was the only sociodemographic characteristic consistently associated with type of use across sites. Specifically, polygynous marriage (compared to monogamous) increased odds of using covertly, ranging from adjusted odds ratio (aOR) of 1.8 [95% confidence interval (CI) 1.2-2.7] in Burkina Faso to 6.2 [95% CI 2.9-13.3] in Kinshasa. Unmarried women with partners or boyfriends were also more likely to be using covertly compared with their monogamously married counterparts in all sites (aORs ranged from 2.2 [95% CI 1.0-4.7] in Uganda to 4.4 [95% CI 1.7-11.0] in Kinshasa). Conclusion: Understanding factors associated with covert use has programmatic and policy implications for women's reproductive autonomy. Implications: Covert use is a common phenomenon across most sites, representing a small but programmatically important contingent of users. Family planning providers and programs must protect access to and maintain privacy of reproductive services to this population, but should also focus on creating interventions and environments that support overt use.